2020
DOI: 10.5713/ajas.19.0263
|View full text |Cite
|
Sign up to set email alerts
|

Replacement value of cassava for maize in broiler chicken diets supplemented with enzymes

Abstract: Objective: Pellet durability, particle size distribution, growth response, tibia bone characteristics and energy retention were measured to evaluate cassava as an alternative energy source to replace maize in broiler diets with or without Ronozyme (A+VP) enzyme composites.Methods: A total of 480 one-day broiler chicks were randomly assigned to 8 treatments in a 4×2 factorial arrangement. Four levels of cassava: (0%, 25%, 50%, 75%) and 2 levels of enzymes (0 and 500 g/tonne) were used. Each treatment was replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
0
5
0
2
Order By: Relevance
“…In contrast, Uchegbu et al ( 4 ) found poor body weight gain in broiler chickens fed cassava fortified with palm oil. Other studies have found significantly reduced growth performance traits in broiler chickens fed cassava ( 17 , 18 ). This wide variability may be due to differences in origin, parts of the cassava plant used, age of harvested crop, diet composition, and processing methods.…”
Section: Introductionmentioning
confidence: 80%
“…In contrast, Uchegbu et al ( 4 ) found poor body weight gain in broiler chickens fed cassava fortified with palm oil. Other studies have found significantly reduced growth performance traits in broiler chickens fed cassava ( 17 , 18 ). This wide variability may be due to differences in origin, parts of the cassava plant used, age of harvested crop, diet composition, and processing methods.…”
Section: Introductionmentioning
confidence: 80%
“…Chemical and physical processing methods (Nambisan, 2011) and genetically modified cassava varieties (Gomez et al, 2021; Siritunga & Sayre, 2004) have also shown reduced cyanide levels in cassava. The cassava peel mash can be mixed with animal feed to improve its nutrient value and was shown to effectively replace maize feed (Chang'a et al, 2020). The efforts on large‐scale conversion of cassava peels into animal feed was initiated by the International Livestock Research Institute (ILRI) and IITA under the CGIAR Research Program on Roots, Tubers and Bananas (RTB) in Nigeria (Amole et al, 2019).…”
Section: Enhancing Other Important Traits In Cassavamentioning
confidence: 99%
“…Bahan pakan lokal potensial lainnya sebagai substitusi jagung adalah singkong. Penggantian jagung dengan singkong sebesar 50% dalam pakan dapat meningkatkan kualitas karkas ayam broiler (Augustine et al 2011) dan tidak mempengaruhi performa pertumbuhan broiler (Chang'a et al 2020). Pemberian tepung singkong mampu menghasilkan performa yang sama seperti ayam broiler yang diberi jagung dalam ransum selama lima minggu (Rahmadani et al 2021).…”
Section: Pendahuluanunclassified
“…Pada ransum berbasis gaplek menunjukkan PBB lebih rendah (p<0,01) jika dibandingkan perlakuan ransum komersial. Hasil ini mengkonfirmasi penelitian (Chang'a et al, 2020) yang menyatakan bahwa ransum berbasis gaplek dengan jumlah berlebih dari 50% sebagai pensubtitusi jagung akan menurunkan PBB harian ayam broiler, pada penelitian ini, hanya menggunakan gaplek tanpa jagung. Hasil ini sesuai juga dengan (Broch et al 2017) yang menyatakan bahwa terjadi pengurangan PBB ayam broiler ketika meningkatkan porsi singkong dalam ransum berbasis jagung.…”
Section: Pertambahan Bobot Badan (Pbb)unclassified